2020
DOI: 10.3390/foods9121880
|View full text |Cite
|
Sign up to set email alerts
|

Seasonal Sensory Evaluation of Low Commercial Value or Unexploited Fish Species from the Portuguese Coast

Abstract: Overfishing is increasing over time, and according to FAO (Food and Agriculture Organization), about one third of the world’s fish stocks are now overfished. Thus, diversifying the target species is essential for fisheries sustainability contributing to improve resource-efficient processes. Non-target species can be valuable resources for the development of new food products. However, those species are scarcely studied, and it is of high importance to trace their seasonal sensory profile as a first step toward… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
7
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
6

Relationship

1
5

Authors

Journals

citations
Cited by 6 publications
(9 citation statements)
references
References 27 publications
(31 reference statements)
0
7
0
Order By: Relevance
“…This is a pioneer study in terms of the seasonal evaluation of fish freshness, since other similar studies are almost nonexistent, which makes the comparison of these and other results quite difficult. In a recent study, Silva et al [ 22 ] performed a seasonal sensory evaluation of five low commercial value or unexploited fish species. The results are difficult to compare with the current study.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…This is a pioneer study in terms of the seasonal evaluation of fish freshness, since other similar studies are almost nonexistent, which makes the comparison of these and other results quite difficult. In a recent study, Silva et al [ 22 ] performed a seasonal sensory evaluation of five low commercial value or unexploited fish species. The results are difficult to compare with the current study.…”
Section: Discussionmentioning
confidence: 99%
“…The results are difficult to compare with the current study. Nevertheless, Silva et al [ 22 ] obtained significant seasonal differences in the sensory evaluation attributes. In addition, Durmus et al [ 4 ] evaluated the effects of seasonal dynamics on sensory, chemical, and microbiological parameters of sardines and concluded that samples from winter deteriorated more rapidly than those from the spring season.…”
Section: Discussionmentioning
confidence: 99%
“…The study was carried out throughout 1 year since the nutritional parameters may vary along seasons. In previous studies, the selected fish species were shown to be sensorially appealing (Silva et al ., 2020), and good sources to be used in the development of marine‐based food products with high acceptance from consumers (Silva et al ., 2021).…”
Section: Introductionmentioning
confidence: 99%
“…based on paper-and-pencil or online questionnaires [2,3,10,[12][13][14]17], and two (~10%) used qualitative focus group interview approaches [11,19]. Furthermore, of the nine studies that included sensory analysis, two studies exclusively applied analytical sensory evaluation techniques using trained or semi-trained sensory panels [6,18], six studies employed hedonic tests to assess acceptability using non-trained panels (consumers) [5,[7][8][9]15,16], while only one study used both [20]. Methods used in the studies demonstrate that the usual techniques of sensory and consumer research are also applicable to research on sustainable foods.…”
mentioning
confidence: 99%
“…Silva et al [18] studied sensory properties of unexploited fish species from the Portuguese coast during a year using check-all-that-apply (CATA) methods tailored to each species. The authors found seasonal influence on sensory attributes in four out of the five studied species and made conclusions on what time of the year would be most favorable for catching a specific fish species in sensory quality's point of view.…”
mentioning
confidence: 99%